Analysis of diamond wheel wear and surface integrity in laser-assisted grinding of RB-SiC ceramics. Issue 18 (15th December 2019) - Rao, Xiaoshuang; Zhang, Feihu; Lu, Yanjun; Luo, Xichun; Ding, Fei; Li, Chen
Abstract: Laser-assisted grinding provides a promising solution for achieving cost-efficient machining of hard and brittle materials. However, the heat generated by laser may cause the wear of diamond grinding wheel, including the wear of both diamond grits and bond material. Consequently, wheel wear has a knock-on effect on the ground surface roughness. Moreover, the laser irritation may also induce damage in the machined surface. This paper focuses on the investigation of wear of diamond grinding wheel and surface integrity in laser-assisted grinding of RB-SiC ceramics. Different temperatures were obtained by setting the laser power to explore the influence of heat on wheel wear and surface integrity. The wear modes and mechanism of the diamond grits and bond material were analyzed by combination of SEM detection and energy dispersion spectrum analysis. The results revealed that adhesion and pullout of diamond grits in laser-assisted grinding were the remarkable difference from those in conventional grinding due to the thermal softening of both RB-SiC specimen and bond material of the grinding wheel. Surface roughness was then improved owing to the increase in active grits. The Raman spectra of the machined surface also revealed different stress conditions and microstructures of the Si and SiC Phase in RB-SiC ceramics. These results provided insight on quality control in laser-assisted machining of RB-SiC ceramics.